THE IMPLEMENTATION OF AKHLAQ LEADERSHIP INELEMENTARY ISLAMIC EXCELLENT SCHOOLS IN MALANG INDONESIA - Triyo Supriyatno (Abjadia, 2016)
Islamic principals practice various leadership styles, ranging from trait to transformational leadership styles. The shifts from one style to another have demonstrated some weaknesses of each style and led to the societal rejection of certain styles in response to environmental changes. This study aimed at introducing a new akhlaq leadership style involving four schools and four leaders at Malang Elementary Islamic excellent school. Data were collected using interview, observation, and documentation. Data were analyzed using qualitative analyze descriptive. The results show that there is significant difference in akhlaq leadership practices according to understanding, appreciation, and experience. However, there exists significant relationship between akhlaq leadership and principal’s working experience. For the principal’s leadership practice priority, the researcher has found that community development is the most commonly practiced akhlaq leadership dimension by the principals. It is followed by the demonstration of fairness, sincerity, respect and serving other dimensions. The major implication is that experienced principals frequently practiced akhlaq leadership compared to less experienced principals, and those who are on the verge of retirement. Hence, the selection of principals should be based their achievement, not seniority in the education service. تهدف هذه الدراسة إلى إدخال أسلوب القيادة الأخلاقية الذي يشمل أربع مدارس وأربعة قادة في المدرسة الإسلامية المتكاملة الابتدائية (SDIT) مالانج. يتم جمع البيانات عن طريق المقابلة والملاحظة والوثائق. تم تحليل البيانات مع التحليل النوعي الوصفي. أظهرت النتائج وجود اختلافات كبيرة في ممارسة القيادة الأخلاقية وفق الفهم والتقدير والخبرة. وجد الباحثون أن تنمية المجتمع هي البعد الأكثر شيوعًا في القيادة التي يمارسها المدير. تبع ذلك إظهار العدالة والإخلاص والاحترام والموقف من الخدمة. وهذا يعني أن الرؤساء ذوي الخبرة غالباً ما يطبقون القيادة الأخلاقية مقارنةً بالمديرين الأقل خبرة أو الأشخاص الذين تقاعدوا تقريبًا. لذلك ، يجب أن يستند اختيار الرؤساء على إنجازاتهم وليس على الأقدمية في الخدمات التعليمية.